Parameter Optimization of Orbital TIG Welding on Stainless Steel Pipe - Thien Tran Ngoc; Van-Thuc Nguyen; Thanh Trung Do; Van Huong Hoang; Dinh Ngoc Huy; Ha Tan Phat; Van Thanh Tien Nguyen (Applied Sciences)
Orbital TIG welding is widely applied to weld pipes to pipes in many fields, such as food, chemicals, oil, gas, and transportation. Optimizing welding parameters such as voltage, current, and travel speed is critical to achieve a good-quality weld. This study investigated the impacts of orbital welding parameters and filler wire diameters on the tensile strength of 304 stainless steel pipes. The 304 stainless steel pipe has an outer diameter of 76 mm and a thickness of 2 mm. Filler wire is used with the workpiece, and is available in three diameters of 0.8 mm, 1 mm, and 1.2 mm, wire feed speed from 3.8 mm/s to 5.6 mm/s, current from 90 A to 110 A, and travel speed fixed at 5.5 mm/s. The highest tensile strength of 562 MPa was achieved with heat input of 0.32 kJ/mm and wire feed speed of 3.8 mm/s. In addition, the best parameters via the Taguchi method were found. The parameters’ influence trends on the weld quality were also revealed.